The Service Performance and Customer Satisfaction Model in Islamic Banking - Afif Zaerofi (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study is twofold; 1). to find the measurement scale of service performance and 2). to examine the impact of service performance dimensions on customer satisfaction in Indonesian Islamic banking context. This study employs survey method with cluster sampling technique. Self-administered questionnaire, with 408 Islamic commercial bank customers as respondents, is used to collect the data/information. Confirmatory Factor Analysis (CFA) is adopted to test the dimensionality of service performance and customer satisfaction. Structural Equation Modeling (SEM) approach is employed to examine the impact of service performance dimensions on customer satisfaction. Results reveal 5 dimensions; physical, interactions, process, technology quality and sharia-compliance reflect service performance measurement scale. It is evidence that 3 dimensions; physical, process and sharia significantly impact on customer satisfaction. Interestingly, another 2 dimensions; interaction and technology do not significantly impact on customer satisfaction. Keywords: Service Performance; Customer Satisfaction; Islamic Banks; Structural Equation Modelling (SEM)